2021
DOI: 10.2174/1570159x19666210803091637
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Treatments for Methamphetamine Use Disorder

Abstract: : Almost two decades have passed since the last methamphetamine (METH) abuse epidemic. In recent years, METH abuse in the US has been rapidly increasing and is currently one of the leading causes of death in our country. Available statistical data indicates re-emergence of METH popularity and suggest an impending third epidemic of METH abuse. Alarmingly, there is no FDA- approved medication for METH use disorder (MUD). This disorder is currently treated with behavioral therapies; however, these therapies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 120 publications
0
10
0
2
Order By: Relevance
“…Past research in rodents showed active immunization using conjugated vaccines can reduce the physiological and behavioral effects of methamphetamine [3,10,[12][13][14][15]58,68]. IXTv-100 GLA-SE and TT-SMA with alum and adjuvant E6020 were safe, had an affinity for the drug, and produced an immune response [13,[59][60][61][62].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Past research in rodents showed active immunization using conjugated vaccines can reduce the physiological and behavioral effects of methamphetamine [3,10,[12][13][14][15]58,68]. IXTv-100 GLA-SE and TT-SMA with alum and adjuvant E6020 were safe, had an affinity for the drug, and produced an immune response [13,[59][60][61][62].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…In the early 20th century, meth was derived from its precursor drug, amphetamine, and initially was used as nasal decongestants and bronchial inhalers ( Vearrier et al, 2012 ). Meth use has been rapidly increasing, attributed to the relatively simple and low-cost manufacturing process ( Moszczynska, 2021 ). Global estimates suggest that more than 35 million people use meth and its analogs worldwide ( Richards and Laurin, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Diagnostic and Statistical Manual of Mental Disorders, fifth Edition (DSM-5) defines substance-related and addictive disorders in two sub-categories: substance use disorders (SUD) and substance-induced disorders. SUD is a chronic and recurrent disorder characterized by increased intake of legal and illicit drugs despite adverse consequences [ 1 , 2 ]. Methamphetamine is a potent central nervous system psychostimulant that affects the brain’s neurotransmitter system.…”
Section: Introductionmentioning
confidence: 99%
“…Methamphetamine is a potent central nervous system psychostimulant that affects the brain’s neurotransmitter system. It is highly addictive and neurotoxic to the central nervous system [ 2 , 3 ]. Methamphetamine, also known as “ice” or “crystal,” has seen a steady increase in abuse in recent years, with more than 33 million people worldwide [ 3 ].…”
Section: Introductionmentioning
confidence: 99%